2001
DOI: 10.1021/ed078p263
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Rubber Elasticity

Abstract: A thermodynamic study of an isotropic rubber band under uniaxial stress is presented on the basis of its equation of state. The behavior of the rubber band is compared with both that of an ideal elastomer and that of an ideal gas, considering the generalized Joule's law as the ideality criterion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Here, the rising relaxation modulus as temperature increases is referred to as thermoelastic inversion, which relates to the elastomer's entropy‐elastic properties . The relation in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the rising relaxation modulus as temperature increases is referred to as thermoelastic inversion, which relates to the elastomer's entropy‐elastic properties . The relation in Eq.…”
Section: Resultsmentioning
confidence: 99%
“… < 1.1, a negative value of  was found experimentally. The transition from a negative to a positive value of the temperature coefficient is known as thermoelastic inversion (Pellicer, 2001) . The phenomenon of thermoelastic inversion is not predicted by theory but, it was shown early (Anthony et al, 1942) and has been confirmed by own measurements (Vennemann & Heinz, 2008), this apparent contradiction results only from thermal expansion of the sample.…”
Section: Rubber Elasticitymentioning
confidence: 99%
“…The aim of the present study is to determine the mechanical behaviour of nitrile elastic bands as a function of their natural length l 0 , the time during which the load is applied (which we call load time t l in this paper) and their mechanical hysteresis cycles. Furthermore, an analysis is performed using a state equation, which, based on previous studies of the thermodynamic behaviour of rubber bands [8,9], is given by the equation…”
Section: Theoretical Aspectsmentioning
confidence: 99%